Differentiation of pluripotent stem cells for modeling human skin development and potential applications - Oceguera-Yanez, Fabian; Avila-Robinson, Alfonso; Woltjen, Knut (Frontiers in Cell and Developmental Biology, 2022)
The skin of mammals is a multilayered and multicellular tissue that forms an environmental barrier with key functions in protection, regulation, and sensation. While animal models have served to study the basic functions of the skin in vivo, they present fundamental differences compared to human skin including structure, appendages, and wound healing. Human pluripotent stem cells (PSCs) have proven to be invaluable tools for studying human development in vitro. To understand the mechanisms regulating human skin homeostasis and injury repair at the molecular level, recent efforts aim to differentiate PSCs towards skin epidermal keratinocytes and skin appendages such as hair follicles, sweat, and sebaceous glands. Here, we present an overview of the literature describing strategies for human PSC differentiation towards the components of skin. We highlight fundamental advances in the field employing patient-derived human induced PSCs (iPSCs) and skin organoid generation. Importantly, PSCs allow researchers to recapitulate events occurring during human fetal development and to model inherited skin diseases in the search for potential treatments. Skin differentiation from human PSCs holds the potential to clarify human-specific skin biology.